Association of Periodontitis and Subsequent Depression: A Nationwide Population-Based Study. Issue 51 (December 2015) - Hsu, Chih-Chao; Hsu, Yi-Chao; Chen, Hsuan-Ju; Lin, Che-Chen; Chang, Kuang-Hsi; Lee, Chang-Yin; Chong, Lee-Won; Kao, Chia-Hung
Abstract : Abstract: Periodontitis is a systemic and chronic inflammatory disease associated with multiple physical conditions. Distress and depression are other problems affecting the progression of periodontitis. However, the causal relationship between depression and periodontitis has not been adequately investigated. This aim of this study was to determine the association between periodontitis and the subsequent development of depression. We identified 12, 708 patients with newly diagnosed periodontitis from 2000 to 2005 and 50, 832 frequency-matched individuals without periodontitis. Both groups were followed until diagnosed with depression, withdrawal from the National Health Insurance program, or the end of 2011. The association between periodontitis and depressio was analyzed using Cox proportional hazard regression models. The incidence density rate of depression was higher in the periodontitis group than in the nonperiodontitis group, with an adjusted hazard ratio of 1.73 (95% confidence interval 1.58–1.89) when adjusting for sex, age, and comorbidity. Cox models revealed that periodontitis was an independent risk factor for depression in patients, except for comorbidities of diabetes mellitus (DM), alcohol abuse, and cancer. Periodontitis may increase the risk of subsequent depression and was suggested an independent risk factor regardless of sex, age, and most comorbidities. However, DM, alcohol abuse, and cancer may prevent the development of subsequent depression because of DM treatment, the paradoxical effect of alcohol, and emotional distress to cancer, respectively. Prospective studies on the relationship between periodontitis and depression are warranted.